The Empirical Analysis of the Relation Between Fdi, Exports and Economic Growth for Romania - Lenuta Carp (CES Working Papers, 2014)
FDIs are considered a key engine to enhance economic growth both in developed and emerging economies, through various channels such as technology transfer, human and physical capital accumulation, commercial channel. The present paper aims at emphasizing the strong, long – term impact of FDI inflows on economic growth through the volume of exports. Using data over the period 1990 – 2012, the article has proved the existence of an important influence exerted by foreign inflows on the GDP growth rates based on a Johansen Co-integration and VECM analysis. Further research will be developed through a panel study on developed and developing economies.
Keywords: F1; F21; F43; 330; FDI; exports; economic growth; Johansen Co-integration